Clinical Factors Associated With Chronic Pain in Communicative Adults With Cerebral Palsy: A Cross-Sectional Study - Chin, Eric M.; Lenz, Colleen; Ye, Xiaobu; Campbell, Claudia M.; Stashinko, Elaine; Jantzie, Lauren L.; Gerner, Gwendolyn; Hoon, Alexander H.; Robinson, Shenandoah (Frontiers in Pain Research, 2020)
Chronic pain is prevalent in adults with cerebral palsy. We aimed to explore associations between chronic pain and somatosensory, motor, cognitive, etiologic, and environmental factors in adults with cerebral palsy. This cross-sectional study enrolled 17 adult participants with cerebral palsy (mean age 31 years; 8 female; Gross Motor Functional Classification Status levels I-V) able to self-report and 10 neurotypical adult volunteers (mean age 34 years; 9 female). Participants reported pain characteristics, demographics, and affective factors. Physical examination included somatosensory and motor evaluation. Between-group comparisons used a ranksum test, and correlation analyses estimated effect size in terms of shared variance (ρ2). Individuals with cerebral palsy reported greater pain intensity, neuropathic qualities, and nociceptive qualities than control participants. Higher pain intensity was associated with female gender (ρ2 = 16%), anxiety/depression symptoms (ρ2 = 10%), and lower household income (ρ2 = 19%). It was also associated with better communicative ability (ρ2 = 21%), spinothalamic (sharp/temperature) sensory abnormalities (ρ2 = 33%), and a greater degree of prematurity (ρ2 = 17%). This study highlights similarity of chronic pain associations in people with cerebral palsy with patterns seen in other populations with chronic pain. Spinothalamic sensory abnormalities suggest central pain mechanisms.